Laser physics - Milonni, Peter W.; Eberly, J. H., 1935- (Hoboken, N.J. : John Wiley & Sons, 2010)
Although the basic principles of lasers have remained unchanged in the past 20 years, there has been a shift in the kinds of lasers generating interest. Providing a comprehensive introduction to the operating principles and applications of lasers, this edition reveals the latest developments and applications of lasers.
Includes bibliographical references and index.
Keywords: Lasers; Nonlinear optics; Physical optics